2021
DOI: 10.1177/25161032211045257
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 on child welfare-involved families: Implications for parent–child reunification and child welfare professionals

Abstract: The COVID-19 pandemic has impacted children and parents involved in the child welfare system and the professionals working with these families. Using survey data collected August–September of 2020, this mixed-methods study examined the perspectives of 196 child welfare-involved professionals (77 attorneys, 99 caseworkers, and 20 therapists) in the United States about the impact of COVID-19 on parents of origin, children, foster parents, and child welfare professionals. Particular attention was paid to the impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 36 publications
(54 reference statements)
0
21
0
Order By: Relevance
“…Throughout the pandemic, the allowance of in-person access visitations has fluctuated, which is problematic because regular and positive contact with birth families often is important for the well-being of young people (Foster Parent Society of Ontario, 2021; Kiraly & Humphreys, 2016). These disruptions to access visitations during the pandemic have also stalled the process of reunification of young people and birth parents (Goldberg, et al, 2021). The problem of access visitation during the pandemic is complicated because there are potential risks associated not only with lack of contact but also with contact.…”
Section: Covid-19 and Resource Parentsmentioning
confidence: 99%
“…Throughout the pandemic, the allowance of in-person access visitations has fluctuated, which is problematic because regular and positive contact with birth families often is important for the well-being of young people (Foster Parent Society of Ontario, 2021; Kiraly & Humphreys, 2016). These disruptions to access visitations during the pandemic have also stalled the process of reunification of young people and birth parents (Goldberg, et al, 2021). The problem of access visitation during the pandemic is complicated because there are potential risks associated not only with lack of contact but also with contact.…”
Section: Covid-19 and Resource Parentsmentioning
confidence: 99%
“…The adoption of digital tools in communication has rapidly accelerated during the COVID-19 pandemic, due to government-directed lockdowns restricting face-to-face contact. This, along with the overall impact of lockdown restrictions, has led to professional concern regarding the mental health, educational progress and family bonds of children who are supported by statutory children’s services ( Goldberg et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Children’s responses to using online methods are likely to vary ( Monserrat et al, 2021 ) and where they have little access to digital methods, feelings of missing and worrying about family have been reported ( Haffeejee & Levine, 2020 ). For children where reunification with parents was a possibility, professionals have expressed strong concerns that a lack of in-person contact jeopardises the prospect of parent-child reunification ( Goldberg et al, 2021 ). However, concerns have also been raised about children being rapidly discharged from care without proper assessment of the home situation and support being in place ( Wilke et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Children and parents in Child Protective Services (CPS) are considered the most vulnerable in this pandemic ( Bolborici, 2020 ; Fegert & Schulze, 2020 ; Frimpong-Manso et al, 2021 ; Goldberg, Brodzinsky, Singer, & Crozier, 2021 ; Goldberg, McCormick, & Virginia, 2021 ; Janssen et al, 2020 ; Langley, Ruderman, Waterman, & Franke, 2021 ; Orlando et al, 2021 ) as the majority families in CPS tend to have ongoing needs (see Caldwell et al, 2020 ). Several scholars believe that the vulnerability of children and families in need has intensified in this global crisis ( Bolborici, 2020 ; Franic & Dodig-Curkovic, 2020 ; Vilar-Compte, Pérez, Teruel, Alonso, & Pérez-Escamilla, 2020 ; Zhang, Li, Shi, Dong, & Wang, 2021 ).…”
mentioning
confidence: 99%
“…COVID-19–related studies have reported an increase in mental health problems, such as anxiety and stress ( Bate et al, 2021 ; Bean et al, 2021 ; Caldwell et al, 2020 ; Gayatri & Irawaty, 2021 ; Huang & Ougrin, 2021 ; Kerr, Fanning, Huynh, Botto, & Kim, 2021 ; McFadden et al, 2021 ; de Winter, de Winter, Bollati, & Milani, 2020 ; Wu & Xu, 2020 ). Parenting stress is heightened, particularly in already at-risk families ( Becker et al, 2020 ; Bik-Multanowska, Mikocka-Walus, Fernando, & Westrupp, 2022 ; Miller, Cooley, & Mihalec-Adkins, 2020 ; Miller, Niu, & Moody, 2020 ; Sonnenschein, Stites, Grossman, & Galczyk, 2022 ; Valeriote & Milligan, 2021 ; Yael, Carmit-Noa, Roni, & Shirli, 2022 ), and has been found to result from issues related to remote schooling and worries about health and children’s well-being ( Garbe et al, 2020 ; Goldberg et al, 2021a , 2021b , 2022 ; Wang et al, 2022 ). Several studies ( Hails et al, 2022 ; McRae, Overall, Henderson, Low, & Chang, 2021 ; Zafar et al, 2022 ; Weeland, keijsers, & Branje, 2021 ) have found that greater levels of parental distress during the pandemic have negatively affected parenting practices.…”
mentioning
confidence: 99%